Amplitude analysis of the KSKS system produced in radiative J/psi decays - Çetin, Serkant Ali (AMER PHYSICAL SOC, 2018)
An amplitude analysis of the KSKS system produced in radiative J/psi decays is performed using the (1310.6 +/- 7.0) x 10(6) nip decays collected by the BESIII detector. Two approaches are presented. A mass-dependent analysis is performed by parametrizing the KSKS invariant mass spectrum as a sum of Breit-aligner line shapes. Additionally, a mass-independent analysis is performed to extract a piecewise function that describes the dynamics of the KSKS system while making minimal assumptions about the properties and number of poles in the amplitude. The dominant amplitudes in the mass-dependent analysis include the f(0)(1710), f(0)(2200), and f(2)'(1525). The mass-independent results, which are made available as input for further studies, are consistent with those of the mass-dependent analysis and are useful for a systematic study of hadronic interactions. The branching fraction of radiative J/psi decays to KSKS is measured to be (8.1 +/- 0.4) x 10(-4), where the uncertainty is systematic and the statistical uncertainty is negligible.
Keywords: J-PSI; LATTICE